Novel combbutrol calcium crystal form and preparation method thereof
A novel crystal form of kobutrox calcium, prepared by X-ray powder diffraction characteristic peaks under Cu-Kα radiation and methanol crystallization, solves the problem of easy hygroscopicity of existing crystal forms, realizes a highly stable and high-purity kobutrox calcium formulation, and provides another option for formulation.
Patent Information
- Application Number
- CN202410696857.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-31
- Publication Date
- 2025-12-02
AI Technical Summary
Existing cobutricalcium crystal forms have shortcomings in terms of storage and stability, especially crystal forms B, C, and D, which are hygroscopic and affect the stability of the formulation.
A novel calcium kobutrogen crystal form with characteristic peaks at 8.370°, 8.650°, 9.360°, 11.640°, and 20.460° under Cu-Kα radiation was used to prepare a novel crystal form with high stability, high yield, and high purity without ethanol by decomplexing and complexing reactions combined with methanol crystallization.
This study achieves high stability and high purity in the novel crystal form of kobutrox calcium, solves storage and stability issues, provides another option for formulation, and avoids the adverse effects of ethanol content on the formulation.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the pharmaceutical field, specifically relating to a novel crystal form of cobutricalcium and its preparation method. Background Technology
[0002] Corbutamol calcium is an additive in gadobutrol injection, which solves the problem of preventing the release of free gadolinium in the injection solution. Gadobutrol injection contains the following components: gadobutrol, sodium corbutamol calcium, tromethamine, hydrochloric acid, and water for injection.
[0003] It has been found that for most gadolinium-containing contrast agents, adding an excess of calcium complex to the formulation to form a complex ligand is advantageous (EP0270483B2). The role of the calcium complex is to prevent the release of free gadolinium from the formulation.
[0004] The significant difference in stability between cobutrical calcium and gadobutrol is the primary reason why cobutrical calcium can be used in gadobutrol injection. The significant difference in stability between the gadolinium complex and the calcium complex means that the calcium complex will remove any free gadolinium ions by forming a gadolinium complex.
[0005] The Chinese chemical name for calcium cobutrinate is: {10-[(1RS,2SR)-2,3-dihydroxy-1-(hydroxymethyl)propyl]-1,4,7,10-tetraazacyclododecane-1,4,7-triaceticacid}calcium complex; its English chemical name is: {10-[(1RS,2SR)-2,3-dihydroxy-1-(hydroxymethy)propyl]-1,4,7,10-Tetraazacyclododecane-1,4,7,-triaceticacid}calcium complex. Its molecular formula is: C 18 H 32 CaN4O9, molecular weight: 488.55, CAS Registry No.: 151878-23-8, calcium cobutrinate is a white or off-white powder, readily soluble in water, and its structural formula is as follows:
[0006]
[0007] Currently, the original manufacturer's Chinese patent CN 109803958 A and Taiwan patent TW 201815771 A mention four crystal forms of cobutricalcium: A, B, C, and D. Crystal form A has maximum 2θ peak values of 7.6°, 9.1°, 11.1°, 11.3°, 11.9°, and 12.3°, and is a monohydrate of 2.0-2.5% by weight ethanol. Crystal forms B, C, and D lack diffraction data, but are all dihydrates of cobutricalcium (approximately 3.4% water of crystallization and 610 ppm ethanol). Furthermore, only crystal form A is suitable for storage; crystal forms B, C, and D are highly hygroscopic and therefore unsuitable for storage, negatively impacting the formulation. Summary of the Invention
[0008] In view of the above-mentioned deficiencies of the prior art, the purpose of this invention is to provide a novel crystal form of cobutricalcium with good stability, high yield and high purity, providing another possibility for formulation selection.
[0009] According to one aspect of the present invention, a novel crystalline form of kobutrocalcium is provided. Using Cu-Kα radiation, the X-ray powder diffraction spectrum of this novel crystalline form, expressed in 2θ, shows characteristic peaks at 8.370°, 8.650°, 9.360°, 11.640°, and 20.460°. When using differential scanning calorimetry (DSC), the novel crystalline form exhibits an endothermic peak at 286.7°C. When using thermogravimetric analysis (TGA), the novel crystalline form shows a weight loss of 2.3% between 30°C and 137.3°C, and a weight loss of 0.4% between 137.3°C and 274.9°C, after which the sample begins to decompose. Furthermore, this novel crystalline form of kobutrocalcium does not contain ethanol.
[0010] In a preferred embodiment of the novel calcium cobutrinate crystal form of the present invention, preferably, the novel calcium cobutrinate crystal form further contains methanol.
[0011] In the preferred embodiment of the novel calcium cobutrinate crystal form of the present invention, preferably, the methanol content of the novel calcium cobutrinate crystal form is 0-0.3 wt%.
[0012] In the preferred embodiment of the novel calcium cobutrinate crystal form of the present invention, preferably, the water content of the novel calcium cobutrinate crystal form is 1.0-3.0 wt%, and the calcium content of the novel calcium cobutrinate crystal form is 8.04-8.36 wt%.
[0013] According to another aspect of the present invention, the present invention provides a method for preparing the novel crystal form of the cobutri calcium, the method comprising the following steps:
[0014] 1) Gadolinol and anhydrous oxalic acid were subjected to a decomplexation reaction in water at a temperature of 90–100 °C to obtain 10-(1-hydroxymethyl-2,3-dihydroxypropyl)-1,4,7-triacetyl-1,4,7,10-tetraazacyclododecane.
[0015] 2) The obtained 10-(1-hydroxymethyl-2,3-dihydroxypropyl)-1,4,7-triacetyl-1,4,7,10-tetraazacyclododecane was subjected to a complexation reaction with one of calcium carbonate, calcium hydroxide or calcium chloride at a temperature of 70-80°C. After the reaction was completed, a mixture was obtained.
[0016] 3) Adjust the free calcium content of the mixture to 0-0.2 wt% with anhydrous oxalic acid, then filter, and distill under vacuum at 60-100℃ until no obvious liquid flows out; add methanol to the remaining residue, reflux and stir, cool to 20-40℃ to precipitate crystals; filter, and then beat the filter cake with methanol again to obtain crystalline solid.
[0017] In the preferred embodiment of the preparation method of the present invention, preferably, in step 1), the time for the decomplexation reaction is 5 hours.
[0018] In the preferred embodiment of the preparation method of the present invention, preferably, in step 2), the complexation reaction time is 2 to 3 hours.
[0019] In the preferred embodiment of the preparation method of the present invention, preferably, in step 3), the reflux stirring time is 2 hours.
[0020] In the preferred embodiment of the preparation method of the present invention, preferably, in step 3), the vacuum degree of the vacuum distillation is -0.08 to -0.1 MPa.
[0021] The preparation method of this invention successfully prepared a novel crystal form of calcium kobutrinate with good stability, high yield (40-90%), and high purity (99.0-99.9%).
[0022] The preparation method of Chinese patent CN 109803958 A includes: 1) Gadobacterium ether + oxalic acid dihydrate, 7 times the amount of water, react at 80℃ for 3-5 hours, cool and filter, wash the filter cake; 2) Filter the filtrate onto a 252C cation exchange resin, elute until the conductivity is less than 10 μs / cm and the pH is 4.5-5.5, then wash the resin with ammonia water, and collect the eluent with pH=11; 3) Add the calculated amount of calcium carbonate to the above eluent, react at 20-25℃ for 1 hour; adjust the ratio of ligand to calcium to 1:1 with ligand or calcium carbonate, then add activated carbon and distill to remove water; 4) Calculate the amount of water, add methyl ethyl ketone and denatured ethanol, reflux for 60 minutes, adjust the water content to between 9-11%, reflux for 3 hours, and then gradually cool for 14 hours to slowly crystallize. Filter and dry to obtain crystal form A.
[0023] Experiments using powder X-ray diffraction, thermogravimetric analysis, and differential scanning calorimetry (DSC) show that the novel crystal form of the described cobutricalcium differs from the cobutricalcium crystal form A in Chinese patent CN 109803958 A, as indicated by X-ray diffraction, DSC, and TGA. Furthermore, this novel crystal form of cobutricalcium does not contain ethanol. The crystal form involved in this invention differs from the cobutricalcium crystal form in Chinese patent CN109803958 A in both powder X-ray diffraction and differential scanning calorimetry, representing a completely different morphology. Therefore, this invention provides another option for pharmaceutical formulations. Attached Figure Description
[0024] Figure 1 The XRD diffraction pattern of the novel crystal form of calcium kobutrogen according to the present invention;
[0025] Figure 2 This is the DSC spectrum of the novel crystal form of calcium cobutrinate in this invention;
[0026] Figure 3 This is the TGA spectrum of the novel crystal form of calcium cobutrinate of this invention;
[0027] Figure 4 The IR spectrum of the novel crystal form of calcium cobutrinate of this invention;
[0028] Figure 5 This is a high-resolution mass spectrum of calcium kobutrofen. Detailed Implementation
[0029] To further illustrate the present invention, a series of embodiments are given below in conjunction with the accompanying drawings. It should be noted that these embodiments are entirely illustrative. The purpose of providing these embodiments is to fully demonstrate the meaning and content of the present invention, but they do not limit the present invention to the scope of the described embodiments.
[0030] Example 1
[0031] Add 30.0g gadobutrol and 8.0g anhydrous oxalic acid to 90.0g deionized water, heat to 90℃ and react. After the reaction is complete, filter to remove gadolinium oxalate and collect the filtrate. Add 6.5g calcium carbonate and heat to 75℃ and react. After the reaction is complete, adjust the free calcium content to 0.2wt% with anhydrous oxalic acid. Distill under reduced pressure at 75℃ and a vacuum of -0.08 to -0.1MPa until no obvious liquid flows out. Add 48g methanol to the residue and reflux with stirring for 2 hours.
[0032] Cool to 20-30℃, filter, then slurry with 48g of methanol once, filter, and dry to obtain 15.3g of the new crystal form of calcium kobutrinate, with a molar yield of 65% and a purity of 99.4%. The product contains 1.0% moisture, 8.04wt% calcium, and no detectable methanol.
[0033] Example 2
[0034] Add 300g gadobutrol and 80g anhydrous oxalic acid to 900g deionized water, heat to 95℃ and react. After the reaction is complete, filter to remove gadolinium oxalate and collect the filtrate. Add 65g calcium carbonate and heat to 70℃ and react. After the reaction is complete, adjust the free calcium content to 0.2wt% with anhydrous oxalic acid. Distill under reduced pressure at 100℃ and a vacuum of -0.08 to -0.1MPa until no obvious liquid flows out. Add 480g methanol to the residue and reflux with stirring for 2 hours.
[0035] Cool to 20-40℃, filter, then slurry with 480g of methanol once, filter, and dry to obtain 184.8g of the new crystal form of calcium kobutrol, with a molar yield of 78.6% and a purity of 99.5%. The product contains 2.2wt% water, 8.26wt% calcium, and 0.13wt% methanol.
[0036] Example 3
[0037] Add 3.0 kg of calcium cobutrinate and 0.8 kg of anhydrous oxalic acid to 9.0 kg of deionized water, heat to 100°C, and react. After the reaction is complete, filter to remove gadolinium oxalate and collect the filtrate. Add 0.65 kg of calcium carbonate, heat to 80°C, and react. After the reaction is complete, adjust the free calcium content to 0.1% with anhydrous oxalic acid, and distill under reduced pressure at 70°C and a vacuum of -0.08 to -0.1 MPa until no obvious liquid flows out. Add 4.8 kg of methanol to the residue and reflux with stirring for 2 hours.
[0038] Cool to 20-40℃, filter, then slurry with 4.8kg of methanol once, filter, and dry to obtain 2.03kg of the new crystal form of calcium kobutrol, with a molar yield of 86.3% and a purity of 99.6%. The product contains 3.0wt% water, 8.36wt% calcium, and 0.3wt% methanol.
[0039] Example 4
[0040] Add 30.0g gadobutrol and 8.0g anhydrous oxalic acid to 90.0g deionized water, heat to 95℃ and react. After the reaction is complete, filter to remove gadolinium oxalate and collect the filtrate. Add 9.56g calcium chloride and heat to 75℃ and react. After the reaction is complete, adjust the free calcium content to 0.1wt% with anhydrous oxalic acid. Distill under reduced pressure at 75℃ and a vacuum of -0.08 to -0.1MPa until no obvious liquid flows out. Add 48g methanol to the residue and reflux with stirring for 2 hours.
[0041] Cool to 20-30℃, filter, then slurry with 48g of methanol once, filter and dry to obtain 11g of the new crystal form of calcium kobutrinate, with a molar yield of 46.5% and a purity of 99.2%. The product contains 2.2wt% water, 8.24wt% calcium, and 0.16wt% methanol.
[0042] Example 5
[0043] Add 30.0g gadobutrol and 8.0g anhydrous oxalic acid to 90.0g deionized water, heat to 95℃ and react. After the reaction is complete, filter to remove gadolinium oxalate and collect the filtrate. Add 4.8g calcium hydroxide and heat to 70℃ and react. After the reaction is complete, adjust the free calcium content to 0.2wt% with anhydrous oxalic acid. Distill under reduced pressure at 70℃ and a vacuum of -0.08 to -0.1MPa until no obvious liquid flows out. Add 48g methanol to the residue and reflux with stirring for 2 hours.
[0044] Cool to 20-30℃, filter, then slurry with 48g of methanol once, filter, and dry to obtain 9.5g of the new crystal form of calcium kobutrinate, with a molar yield of 40.1% and a purity of 99.6%. The product contains 1.0wt% water, 8.14wt% calcium, and 0.14wt% methanol.
[0045] Example 6
[0046] Add 300g gadobutrol and 80g anhydrous oxalic acid to 900g deionized water, heat to 100℃ and react. After the reaction is complete, filter to remove gadolinium oxalate and collect the filtrate. Add 95.6g calcium chloride and heat to 80℃ and react. After the reaction is complete, adjust the free calcium content to 0.2wt% with anhydrous oxalic acid. Distill under reduced pressure at 100℃ and a vacuum of -0.08 to -0.1MPa until no obvious liquid flows out. Add 480g methanol to the residue and reflux with stirring for 2 hours.
[0047] Cool to 20-40℃, filter, then slurry with 480g of methanol once, filter, and dry to obtain 145g of the new crystal form of calcium kobutrinate, with a molar yield of 61.5% and a purity of 99.5%. The product contains 2.2wt% water, 8.26wt% calcium, and 0.16wt% methanol.
[0048] Example 7
[0049] Add 300g gadobutrol and 80g anhydrous oxalic acid to 900g deionized water, heat to 100℃ and react. After the reaction is complete, filter to remove gadolinium oxalate and collect the filtrate. Add 48g calcium hydroxide and heat to 80℃ and react. After the reaction is complete, adjust the free calcium content to 0.02wt% with anhydrous oxalic acid. Distill under reduced pressure at 100℃ and a vacuum of -0.08 to -0.1MPa until no obvious liquid flows out. Add 480g methanol to the residue and reflux with stirring for 2 hours.
[0050] Cool to 20-40℃, filter, then slurry with 480g of methanol once, filter, and dry to obtain 140g of the new crystal form of calcium kobutrinate, with a molar yield of 59.4% and a purity of 99.3%. The product contains 2.0wt% water, 8.22wt% calcium, and 0.18wt% methanol.
[0051] Example 8
[0052] Add 3.0 kg of calcium cobutrinate and 0.8 kg of anhydrous oxalic acid to 9.0 kg of deionized water, heat to 90°C, and react. After the reaction is complete, filter to remove gadolinium oxalate and collect the filtrate. Add 0.96 kg of calcium chloride, heat to 75°C, and react. After the reaction is complete, adjust the free calcium content to 0.02% with anhydrous oxalic acid. Distill under reduced pressure at 75°C and a vacuum of -0.08 to -0.1 MPa until no obvious liquid flows out. Add 4.8 kg of methanol to the residue and reflux with stirring for 2 hours.
[0053] Cool to 20-40℃, filter, then slurry with 4.8kg of methanol once, filter, and dry to obtain 1.6kg of the new crystal form of calcium kobutrol, with a molar yield of 67.7% and a purity of 99.4%. The product contains 2.8wt% water, 8.35wt% calcium, and 0.12wt% methanol.
[0054] Example 9
[0055] Add 3.0 kg of calcium cobutrinate and 0.8 kg of anhydrous oxalic acid to 9.0 kg of deionized water, heat to 90°C, and react. After the reaction is complete, filter to remove gadolinium oxalate and collect the filtrate. Add 0.48 kg of calcium hydroxide, heat to 75°C, and react. After the reaction is complete, adjust the free calcium content to 0% with anhydrous oxalic acid, and distill under reduced pressure at 75°C and a vacuum of -0.08 to -0.1 MPa until no obvious liquid flows out. Add 4.8 kg of methanol to the residue and reflux with stirring for 2 hours.
[0056] Cool to 20-40℃, filter, then slurry with 4.8kg of methanol once, filter, and dry to obtain 1.5kg of the new crystal form of calcium kobutrinate, with a molar yield of 63.5% and a purity of 99.6%. The product contains 2.1wt% water, 8.25wt% calcium, and 0.15wt% methanol.
[0057] Example 10: Detection Method for IR Analysis
[0058] Testing Unit: Beijing Beilu Pharmaceutical Co., Ltd.
[0059] Instrument: IS10 Fourier transform mid-infrared spectrometer
[0060] Instrument calibration: The instrument wavenumber was calibrated using the infrared absorption peak of the polystyrene film (refer to General Chapter 0402, Part IV, Chinese Pharmacopoeia 2015) (see Table 1).
[0061] Table 1
[0062]
[0063] As can be seen from Table 1: a) 3406.23cm -1 3265.79cm -1 a) Broad absorption peak, indicating -OH stretching vibration. This proves the presence of a hydroxyl group in the structure of this product. b) 2857.71 cm⁻¹ -1 The weak absorption peak indicates the stretching vibration of CH in a saturated hydrocarbon, proving the presence of saturated carbon in the structure of this product. (c) 1599.47 cm⁻¹ -1 The strong absorption peak indicates the asymmetric stretching vibration of C=O in the carboxylate, proving that the product structure contains a carboxyl group. (d) 1378.33 cm⁻¹ -1 The absorption peak of moderate intensity indicates the stretching vibration of the CO bond.
[0064] As can be seen, the above infrared spectral data are consistent with the structure of kobutramine calcium, such as... Figure 4 As shown.
[0065] Example 11: Detection method using powder X-ray diffraction
[0066] Testing Unit: Hanmeng Testing Technology (Tianjin) Co., Ltd.
[0067] Instrument: XD6 polycrystalline X-ray diffractometer
[0068] Target: Cu-Kα
[0069] Wavelength: 0.154nm
[0070] X-ray tube voltage: 36kV
[0071] X-ray tube current: 20mA
[0072] Step size: 0.01
[0073] Scanning speed: 8° / min
[0074] Scanning range: 3°~60°
[0075] The novel crystal form of calcium kobutrol was analyzed using an XD6 polycrystalline X-ray diffractometer. The results showed characteristic peaks at 8.370°, 8.650°, 9.360°, 11.640°, and 20.460°. Figure 1 As shown.
[0076] Example 12: Detection method of differential scanning calorimetry
[0077] Testing Unit: Hanmeng Testing Technology (Tianjin) Co., Ltd.
[0078] Instrument: Differential scanning calorimeter
[0079] Temperature range: 30~320℃
[0080] Heating rate: 10℃ / min
[0081] The novel crystal form of calcium kobutrinate obtained by the present invention was detected by differential scanning calorimetry. The detection results showed that the novel crystal form of calcium kobutrinate of the present invention has an endothermic peak at 286.7℃. Figure 2 As shown.
[0082] Example 13: Detection method of thermogravimetric analysis
[0083] Testing Unit: Hanmeng Testing Technology (Tianjin) Co., Ltd.
[0084] Instrument: Thermogravimetric analyzer
[0085] Temperature range: 30~350℃
[0086] Heating rate: 10℃ / min
[0087] The novel crystalline form of kobutri calcium was analyzed using a thermogravimetric analyzer. The results showed that the novel crystalline form of kobutri calcium exhibited a weight loss of 2.3% between 30℃ and 137.3℃, and a weight loss of 0.4% between 137.3℃ and 274.9℃. After this point, the sample began to decompose. Figure 3 As shown.
[0088] Example 14: Comparison of the crystal form of the present invention with crystal form A of Chinese Patent CN 109803958 A
[0089] 1. The crystal form of the present invention is compared with crystal form A of Chinese Patent CN 109803958 A. The comparison of the three strongest peaks of their powder diffraction characteristics is shown in Table 2 below.
[0090] Table 2
[0091]
[0092] 2. The water content test results of the calcium cobutriate crystal form of the present invention show that the crystal form of the present invention is different from the calcium cobutriate crystal form A containing monohydrate in Chinese patent CN109803958 A, and the dihydrate crystal forms B, C, and D described in the original research TW 201815771A.
[0093] Chinese Patent CN 109803958 A describes a monohydrate form of calcium kobutroxide, crystal form A, with a water content of 3.9-8.2 wt%. The original research patent TW 201815771 A describes dihydrate crystal forms B, C, and D, with a water content of 3.4 wt%. The water content results of the crystal forms in this invention are shown in Table 3 below, with a water content of 1.0-3.0 wt%.
[0094] Table 3
[0095]
[0096]
[0097] 3. Stability test of calcium cocob: As can be seen from Table 4, the calcium cocob of the present invention has good stability. The XRD patterns at 0 days and 18 months are shown in Table 4 below.
[0098] Table 4
[0099]
[0100] 4. The entire preparation process of this invention does not use ethanol, and the finished product of the novel cobutri calcium crystal form was tested and found to contain no ethanol. In contrast, the original manufacturer's Chinese patent CN 109803958 A states that the ethanol content in the finished product is 2.0%–2.5 wt%, and the Taiwan patent TW 201815771 A mentions that the ethanol content in finished products of cobutri calcium crystal forms B, C, and D is 610 ppm.
[0101] Example 15: Study on the functional properties of Corbutri calcium
[0102] Tables 5 and 6 show the drug dosage forms, routes of administration, formulations, and countries of market for cobutricalcium, as well as its routes of administration, uses, characteristic indicators, and applications in formulations.
[0103] Table 5: Dosage Forms, Routes of Administration, Formulations, and Countries of Market for Cobutriol Calcium
[0104]
[0105] Table 6: Routes of administration, uses, properties and applications of Calcium Cobutiax in formulations
[0106]
[0107] From a functional perspective, the equation for the complexation reaction between calcium cobutrinate and free gadolinium is as follows:
[0108]
[0109] Therefore, calcium cobutrinate, as a chelating agent, chelates any form of free gadolinium generated in gadobutrol injection to remove any free gadolinium ions, thereby preventing the release of free gadolinium from the formulation.
[0110] The inventors in this case prepared kobutro calcium with reference to the preparation method of patent CN109803958A, using ethanol as the crystallization solvent, and obtained a white, cotton-like compound. The inventors then conducted tests on the appearance, water content, ethanol content, methanol content, and calcium content of the kobutro calcium sample prepared according to the method of CN109803958A and the kobutro calcium sample prepared according to this invention, as shown in Table 7 below.
[0111] Table 7
[0112]
[0113] As can be seen from the data in Table 7, the properties of the calcium kobutrol obtained by ethanol crystallization in Chinese patent CN109803958A are significantly different from those of the calcium kobutrol obtained by methanol crystallization in this invention.
[0114] Secondly, the inventors noted that, based on the structural formula and HRMS mass spectrum of caustic soda, the theoretical calcium content of caustic soda is 8.2 wt%, as shown in the high-resolution mass spectrum. Figure 5 .
[0115] The inventor's experimental results show that the calcium content of the Cobutri calcium sample in Chinese Patent CN109803958A, at 11.6 wt%, exceeds the theoretical value.
[0116] However, as shown in Examples 5 and 6 of Chinese Patent CN109803958A, the calcium content of the ethanol-crystallized calcium kobutriate samples was 100.64% and 100.80%. This is likely due to different calculation methods. It is speculated that the calcium content calculation method in Chinese Patent Application CN109803958A uses the percentage of the sample's dry calcium content in the molecular formula as a base of 100%. In contrast, the calcium content calculation method in this invention uses the percentage of the sample's calcium content in the molecular formula as a base.
[0117] Therefore, based on the measured calcium content, it is inferred that the ethanol-crystallized calcium kobutrinate is likely a mixture of compound 1 and compound 2, with the following specific structural formula:
[0118]
[0119] Furthermore, after reproducing the preparation method of Chinese patent CN109803958A, it was found that the calcium content of the ethanol-crystallized calcium kobutrinate sample, at 11.6 wt%, also exceeded the theoretical value. Therefore, it can be theoretically determined that the ethanol-crystallized calcium kobutrinate sample is likely a mixture of compound 1 and compound 2 prepared in the patent, specifically including bimolecular calcium kobutrinate and single calcium kobutrinate. The calcium kobutrinate sample of this invention, however, is a single substance.
[0120] It should be noted that the above-described invention content and specific embodiments are intended to demonstrate the practical application of the technical solution provided by this invention and should not be construed as limiting the scope of protection of this invention. Those skilled in the art can make various modifications, equivalent substitutions, or improvements within the spirit and principles of this invention. The scope of protection of this invention is defined by the appended claims.
Claims
1. A novel crystal form of calcium kobutrinate, characterized in that, Using Cu-Kα radiation, the X-ray powder diffraction spectrum of this novel calcium kobutriol, expressed as 2θ, shows characteristic peaks at 8.370°, 8.650°, 9.360°, 11.640°, and 20.460°. Differential scanning calorimetry (DSC) shows an endothermic peak at 286.7 °C. Thermogravimetric analysis (TGA) shows a 2.3% weight loss between 30 °C and 137.3 °C, and a 0.4% weight loss between 137.3 °C and 274.9 °C, after which the sample begins to decompose. Furthermore, this novel calcium kobutriol does not contain ethanol.
2. The novel crystal form of kobutro calcium as described in claim 1, characterized in that, This novel crystal form of calcium cobutrinate also contains methanol.
3. The novel crystal form of kobutro calcium as described in claim 2, characterized in that, The methanol content of this novel crystal form of calcium kobutrogen is 0-0.3 wt%.
4. The novel crystal form of kobutro calcium as described in any one of claims 1-3, characterized in that, The water content of this novel calcium sorbitol crystal form is 1.0-3.0 wt%, and the calcium content of this novel calcium sorbitol crystal form is 8.04-8.36 wt%.
5. A method for preparing a novel crystal form of calcium kobutrogen as described in any one of claims 1-4, characterized in that, The preparation method includes the following steps: 1) Gadolinol and anhydrous oxalic acid were subjected to a decomplexation reaction in water at a temperature of 90–100 °C to obtain 10-(1-hydroxymethyl-2,3-dihydroxypropyl)-1,4,7-triacetyl-1,4,7,10-tetraazacyclododecane. 2) The obtained 10-(1-hydroxymethyl-2,3-dihydroxypropyl)-1,4,7-triacetyl-1,4,7,10-tetraazacyclododecane was subjected to a complexation reaction with one of calcium carbonate, calcium hydroxide or calcium chloride at a temperature of 70-80°C. After the reaction was completed, a mixture was obtained. 3) Adjust the free calcium content of the mixture to 0-0.2 wt% with anhydrous oxalic acid, then filter, and distill under vacuum at 60-100℃ until no obvious liquid flows out; add methanol to the remaining residue, reflux and stir, cool to 20-40℃ to precipitate crystals; filter, and then beat the filter cake with methanol again to obtain crystalline solid.
6. The preparation method according to claim 5, characterized in that, In step 1), the time for the decomposition reaction is 5 hours.
7. The preparation method according to claim 5, characterized in that, In step 2), the complexation reaction takes 2 to 3 hours.
8. The preparation method according to claim 5, characterized in that, In step 3), the reflux stirring time is 2 hours.
9. The preparation method according to claim 5 or 8, characterized in that, In step 3), the vacuum degree of the vacuum distillation is -0.08 to -0.1 MPa.
Citation Information
Patent Citations
Method for producing the crystalline form of modification a of calcobutrol
CN109803958A
Pharmaceutical compounds containing metals
EP0270483B2
Method for producing the crystalline form of modification a of calcobutrol
TW201815771A